1997
DOI: 10.1046/j.1365-2222.1997.990906.x
|View full text |Cite
|
Sign up to set email alerts
|

TH2-polarized immunological memory to inhalant allergens in atopics is established during infancy and early childhood

Abstract: Inhalant allergen-specific in vitro cytokine production associated with positive skin-prick test (SPT) reactions, one of the hallmarks of adult atopy, manifests in children at or before 5 years of age; additionally, cytokine responses in SPT negative 5 year-olds are restricted to IFNgamma, as per normal adults. In contrast, T-cell responses to a typical food allergen appear to be deleted during early childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
142
3
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(155 citation statements)
references
References 0 publications
8
142
3
2
Order By: Relevance
“…Firstly, these show that initial low-level responses in CBMC are dominated by Th2 cytokines [13], but are subsequently modified during infancy and early childhood. Thus, Th2 reactivity is steadily boosted in children who progress to early expression of atopy symptoms [14] and/or skin-prick test positivity to inhalants [17,18]; whereas, these responses are diverted ("immune deviated") towards a Th1-like pattern in the nonatopics. This Th memory generation process in many individuals appears to be complete by the end of the preschool or early school years, potentially locking individuals into lifelong patterns of allergen responsiveness.…”
Section: T-cell Immunity To Inhalant Allergens: the Basis Of Variatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, these show that initial low-level responses in CBMC are dominated by Th2 cytokines [13], but are subsequently modified during infancy and early childhood. Thus, Th2 reactivity is steadily boosted in children who progress to early expression of atopy symptoms [14] and/or skin-prick test positivity to inhalants [17,18]; whereas, these responses are diverted ("immune deviated") towards a Th1-like pattern in the nonatopics. This Th memory generation process in many individuals appears to be complete by the end of the preschool or early school years, potentially locking individuals into lifelong patterns of allergen responsiveness.…”
Section: T-cell Immunity To Inhalant Allergens: the Basis Of Variatiomentioning
confidence: 99%
“…The following principal observations underpin the atopy component of this scheme. 1) Allergen-specific Th-cell priming occurs in the perinatal period [8][9][10][11][12][13], and these early immune responses become compartmentalized into Th1-or Th2-polarized memory during the preschool years [14][15][16][17][18].…”
Section: The Apparent Dualistic Effects Of Respiratory Tract Infectiomentioning
confidence: 99%
“…Short fetal CDR3 regions may result in flat Agbinding sites (13). This may explain the frequent presence of lowaffinity polyreactive specificities in naive frequent thymic emigrants in the fetal immune system (14,15). This low-affinity response is illustrated in T cell epitope mapping of OVA, a common food allergen, in cord compared with adult blood.…”
mentioning
confidence: 99%
“…This low-affinity response is illustrated in T cell epitope mapping of OVA, a common food allergen, in cord compared with adult blood. CBMC demonstrate broadly reactive responses to multiple OVA peptides that are absent in adults (15), suggesting fetal lymphocytes' lack of fine antigenic specificity to certain Ags.…”
mentioning
confidence: 99%
“…Another study revealed a predominant CD4+ positive T cells, eosinophil rich infiltrate and increased IgE response which suggests a Thelper 2 (T-h2) mediated response to the salivary protein 5 . Moreover atopic individuals have a high IgE production and a persistent Th2 response (6)(7).…”
Section: Mechanism Of Papular Urticariamentioning
confidence: 99%